Korelasi Kelincahan, Keseimbangan, dan Kecepatan terhadap Kemampuan Menggiring Bola pada SSB BINA PUTRA - bintara, johan yudha; Hartono, Mugi (Indonesian Journal for Physical Education and Sport, 2023)
The purpose of this study was to determine a significant relationship between agility, balance, and speed with the ability to dribble in SSB Bina Putra Wonosobo soccer players. The research method uses a descriptive correlational method with a one shoot model approach. In determining the sample in this study using total sampling. The data collection technique used tests and measurements, namely an agility test using The Illinois Course and a speed test using a 40 meter sprint running test and a balance test using a Balance one test and a dribbling test using the soccer dribbling test. For data analysis techniques using correlation. The results of this study indicate that agility has a correlation coefficient with significant results, then for balance it has a correlation coefficient with significant results, and speed has a correlation coefficient with significant results, and the multiple correlation results of agility, balance, and speed variables on the dribbling variable have a correlation coefficient. with significant results. The conclusion of this study is that there is a significant relationship between agility, balance, and speed on dribbling the soccer players of SSB Bina Putra Wonosobo aged 11-12 years.